Up-regulation of endoplasmic reticulum stress induced genes of the unfolded protein response in the liver of periparturient dairy cows - Gessner, Denise; Schlegel, Gloria; Ringseis, Robert; Schwarz, Frieder; Eder, Klaus; Justus Liebig University Giessen (My University, 2014)
BACKGROUND: In dairy cows, the periparturient phase is a stressful period, which is commonly associated with strong metabolic adaptations and the development of pathophysiologic conditions and disorders. Some of the symptoms occurring in the liver, such as the development of fatty liver, are similar to those observed under the condition of endoplasmic reticulum (ER) stress. Therefore, we hypothesized, that in the liver of dairy cows ER stress is induced during the periparturient phase, which in turn leads to an induction of the unfolded protein response (UPR). In order to investigate this hypothesis, we determined relative mRNA concentrations of 14 genes of the ER stress-induced UPR in liver biopsy samples of 13 dairy cows at 3 wk antepartum and 1, 5 and 14 wk postpartum. RESULTS: We found, that the mRNA concentrations of 13 out of the 14 genes involved in the UPR in the liver were significantly increased (1.9 to 4.0 fold) at 1 wk postpartum compared to 3 wk antepartum. From 1 wk postpartum to later lactation, mRNA concentrations of all the genes considered were declining. Moreover, at 1 wk postpartum, mRNA concentration of the spliced variant of XBP1 was increased in comparison to 3 wk antepartum, indicating that splicing of XBP1 - a hallmark of ER stress - was induced following the onset of lactation.CONCLUSION: The present study reveals, that ER stress might be induced during the periparturient phase in the liver of dairy cows. We assume that the ER stress-induced UPR might contribute to the pathophysiologic conditions commonly observed in the liver of periparturient cows, such as the development of fatty liver, ketosis or inflammation.
Keywords: dairy cow; liver; ER stress; unfolded protein response; ddc:630